Prothrombin amino terminal region helps protect coagulation factor Va from proteolytic inactivation by activated protein C - Yegneswaran, Subramanian; Nguyen, Phuong M.; Gale, Andrew J.; Griffin, John H. (Thrombosis and Haemostasis, 2009)
The hypothesis that prothrombin (FII) protects coagulation factor Va (FVa) from proteolytic inactivation by activated protein C (APC) was tested using purified proteins. FII dose-dependently protected FVa from APC proteolysis under conditions where competition of proteins for binding to negatively-charged phospholipid surface was not relevant (i.e. either at high phospholipid vesicle concentrations or using soluble dicaproylphosphatidylserine at levels below its critical micellar concentration). Cleavages in FVa at both Arg506 and Arg306 by APC were inhibited by FII. FII did not alter the amidolytic activity of APC towards chromogenic oligopeptide substrates or inhibit FVIIIa inactivation by APC, implying that the FII-mediated protection of FVa from APC proteolysis was due to the ability of FII to inhibit protein-protein interactions between FVa and APC. FII also protected FVa from inactivation by Gla-domainless APC, ruling out a role for the APC Gla domain for these observations. To identify domains of FII responsible for the observed phenomenon, various forms or fragments of FII were employed. Biotin-PheProArg-CMK-inhibited meizothrombin and fII-fragment 12 protected FVa from proteolysis by APC. In contrast, no significant protection of FVa from APC cleavage was observed for Gladomainless-FII, prethrombin-1, prethrombin-2, FII fragment 1 or active site inhibited-thrombin (DEGR-thrombin). Overall, these data demonstrate that the Gla domain of FII linked to kringle 1 and 2 is necessary for the ability of FII to protect FVa from APC cleavage and support the general concept that assembly of the FII activation complex (FXaFVaFIIlipid surface) protects FVa from APC inactivation so that the procoagulant, thrombin generating pathway can act unhindered by APC. Only following FII activation and dissociation of the FII Gla domain fragments from the FII-ase complex, can APC inactivate FVa and down-regulate thrombin generation.
Keywords: Prothrombin; factor Va; activated protein C; inhibition; inactivation